The association between essential trace element (copper, zinc, selenium, and cobalt) status and the risk of early embryonic arrest among women undergoing assisted reproductive techniques - Cao, Yu; Liang, Chunmei; Shen, Lingchao; Zhang, Zhikang; Jiang, Tingting; Li, Danyang; Zou, Weiwei; Wang, Jieyu; Zong, Kai; Liang, Dan; Ji, Dongmei; Cao, Yunxia (Frontiers in Endocrinology, 2022)
Objective: Our study aimed to investigate the associations of peripheral blood levels of four essential trace elements (Cu, Zn, Se and Co) and their mixtures with the risk of EEA. Methods: A total of 74 EEA cases (123 IVF cycles) and 157 age and BMI matched controls (180 IVF cycles) from the reproductive center of the First Affiliated Hospital of Anhui Medical University in Hefei, China, between June 2017 and March 2020 were included in our study. Levels of Cu, Zn, Se and Co were assessed by measuring them in blood samples collected on the day of oocyte retrieval when infertile women entering clinical treatment for the first time using ICP-MS. Generalized estimating equation (GEE) models were used to evaluate the associations of four essential trace elements concentrations solely with the risk of EEA and Bayesian kernel machine regression (BKMR) were used to explore the associations between four essential trace element mixtures and the risk of EEA, respectively. Results: Based on single-metal models, Co was positively associated with the risk of EEA before and after adjustment of all the confounders (OR=1.72, 95%CI=1.18, 2.52; OR=2.27, 95%CI=1.37, 3.77; respectively), Se was negatively associated with the risk of EEA before adjustment of all the confounders (OR=0.18, 95%CI=0.07, 0.51). The BKMR analyses showed that Se was significantly and negatively associated with the risk of EEA when all the other three metals were fixed at 25th, 50th or 75th percentiles, while Zn displayed a significant and positive association with the risk of EEA when all the other three metals were fixed at 25th, 50th or 75th percentiles, Co did not show any effect on the risk of EEA when all the other metals were fixed at 25th, 50th or 75th percentiles; in addition, a positive joint effect of four essential trace elements on the risk of EEA was found, but it was not statistically significant. Conclusion: We found that the levels of essential trace elements are correlated with the risk of EEA to some extent. Infertile women should keep appropriate levels of Cu, Zn, Se and Co to avoid EEA, especially for Se and Zn.